Long-Term Outcomes of Catheter Ablation of Ventricular Tachycardia in Patients With Cardiac Sarcoidosis. (August 2016) - Muser, Daniele; Santangeli, Pasquale; Pathak, Rajeev K.; Castro, Simon A.; Liang, Jackson J.; Magnani, Silvia; Hayashi, Tatsuya; Garcia, Fermin C.; Hutchinson, Mathew D.; Supple, Gregory E.; Frankel, David S.; Riley, Michael P.; et al.
Abstract : Background—: Catheter ablation (CA) of ventricular tachycardia (VT) in patients with cardiac sarcoidosis can be challenging because of the complex underlying substrate. We sought to determine the long-term outcome of CA of VT in patients with cardiac sarcoidosis. Methods and Results—: We enrolled 31 patients (age, 55±10 years) with diagnosis of cardiac sarcoidosis based on Heart Rhythm Society criteria and VT who underwent CA. In 23 (74%) patients, preprocedure cardiac magnetic resonance imaging and positron emission tomographic (PET) evaluation were performed. Preprocedure magnetic resonance imaging was positive for late gadolinium enhancement in 21 of 23 (91%) patients, whereas abnormal 18-fluorodeoxyglucose uptake was found in 15 of 23 (65%) cases. In 14 of 15 patients with positive PET at baseline, PET was repeated after 6.1±3.7-month follow-up. After a median follow-up of 2.5 (range, 0–10.5) years, 1 (3%) patient died and 4 (13%) underwent heart transplant. Overall VT-free survival was 55% at 2-year follow-up. Among the 16 (52%) patients with VT recurrences, CA resulted in a significant reduction of VT burden, with 8 (50%) having only isolated (1–3) VT episodes and only 1 patient with recurrent VT storm. The presence of late gadolinium enhancement at magnetic resonance imaging, a positive PET at baseline, and lack of PET improvement over follow-up were associated with increased risk of recurrent VT. Conclusions—: In patients with cardiac sarcoidosis and VT, CA is effective in achieving long-term freedom from VT or improvement in VT burden in the majority of patients. The presence of late gadolinium enhancement at magnetic resonance imaging, a positive PET scan at baseline, or lack of improvement at repeat PET over follow-up predict worse arrhythmia-free survival. Abstract : Supplemental Digital Content is available in the text.